2017
DOI: 10.1136/bcr-2017-220153
|View full text |Cite
|
Sign up to set email alerts
|

Hickam's dictum: Myasthenia Gravis presenting concurrently with Graves' disease

Abstract: We present two patients with Graves' disease and concurrent myasthenia gravis. The impact of the dual diagnosis on the clinical course and the potential for a delayed diagnosis of myasthenia gravis is discussed. Patient 1, a 28-year-old man was diagnosed with Graves' disease following his second respiratory arrest. His history was strongly suggestive of a second pathology. Patient 2, a 66-year-old Cantonese woman with established Graves' disease presented with thionamide-related neutropaenia. Examination revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The possible association of neuromuscular disease with thyroid disorders was first described in 1953. In the subsequent decades, this link has frequently been reported [1]. Graves' disease occurs in approximately 5-8% of patients with myasthenia gravis [2].…”
Section: Discussionmentioning
confidence: 99%
“…The possible association of neuromuscular disease with thyroid disorders was first described in 1953. In the subsequent decades, this link has frequently been reported [1]. Graves' disease occurs in approximately 5-8% of patients with myasthenia gravis [2].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular signs can create diagnostic confusion in cases of concomitant MG in Graves’. [12] In other words, emergence of neuromuscular and bulbar symptoms during the treatment of thyrotoxicosis should alert the physician to suspect coexisting MG.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study was done from 2008 to 2009 on 300 patients of MG for linkage of MG with thyroid disease. Study results showed that MG patients with positive thyroid antibodies have a higher number of AchR antibodies and more abnormalities with T cells [25]. Of all the thyroid diseases, Graves' disease is more frequent in patients with MG. Clinical features like neuromuscular weakness and ocular signs cause diagnostic confusion between two pathologies [24].…”
Section: Treatment Advances For Mgmentioning
confidence: 91%
“…This respiratory failure resulted after giving medication for his thyrotoxicosis, which unmasked the myasthenia gravis. Physicians should also consider MG in hyperthyroid patients presenting with neuromuscular weakness [25]. So, there is diagnostic confusion between MG and Graves' disease because of similarities in clinical features, and co-occurrence of these two autoimmune pathologies seen often in the same individual.…”
Section: Treatment Advances For Mgmentioning
confidence: 99%